The Problem of Choice between Personal Benefit and Professional Responsibility in Lawyers Work: Development of Individual Level of Control - Anton Kazun (Journal of Economic Sociology, 2013)
In practice, legal community often faces a dilemma: to follow personal interests or the rules prescribed by professional ethics. The contradiction inherents in the principle of professional work: on the one hand, lawyer is obliged to fulfill all wishes of the client; on the other hand, professional activity should be the main source of his income. A contradiction concerning time-consuming, remuneration,emotional involvement and other issues often arises between the interests of the client and the interests of professional. Final lawyer’s choice depends on current forms of control: external (society), internal (colleagues) and individual (professional himself). Individual level of control is always crucial because it is quite difficult to evaluate the quality of lawyers work for clients or even colleagues. Formal, informal and individual levels of control are defined by different actors —the state, the professional community and law faculties, respectively. That is why it makes sense to start the analysis of problem of choice between self-interest and professional responsibility with law students. Using the strategy of mixed method we consider the process of professional values formation among law students of three different universities. Our analysis is based on questionnaire survey of 282 law students in three universities of Russia: Higher School of Economics, People’s Friendship University, and Russian Academy of Justice. Qualitative data part consists of 8 interviews with law students and 6 video interviews with the winners of the award “Lawyer of the Year” taken from the site of the “Lawyers Association of Russia”. It is used to create research tools and to make interpretations of the results from quantitative data. The strategy of quantitative case-study allows us to draw a conclusion what the atmosphere within the university and the level of student’s involvement in the university’s life predetermine professional values, and hence the choice in favor of one or another variant of behavior. In addition, we found out that the majority of law students formed a negative image of the lawyer as a businessman or a deceiverby the last year of education. This fact gives grounds to assume that the informal level of control in the legal environment could be poorly developed because of the low initial expectations of young professionals.